Government Policies for Economic Recovery and Handling COVID -19 Virus in Indonesia - Desy Tri Anggarini; Ani Rakhmanita (Universitas Bina Sarana Informatika, 2020)
WHO establishes coronavirus (coronavirus disease, COVID-19), as the Public Health Anxiety of the World on January 30, 2020. The increase in countries affected by the Covid-19 virus is widespread throughout the world such as America, Spain and Italy making the world economic situation even more get worse. Some institutions predict the weakening of the world economy. The contraction of the global economy is still ongoing, uncertainty in the global financial markets has declined as the sluggish spread of COVID-19. The limitation of economic activity as a step for handling COVID-19 risks reducing global economic growth in 2020. Research on Government Policy for Economic Recovery and handling COVID-19 Virus in Indonesia, taking stimulus from fiscal and monetary policies undertaken by the Bank Indonesian , Ministry of Finance and Regulations Government 2020, with descriptive qualitative research methods using secondary data such as literature books, review studies from the internet and policies from the government and related ministries. The results of this study have carried out monetary policy through Bank Indonesia, and fiscal policy through the Ministry of finance and supported by Government Regulation of the Republic of Indonesia Number 23 of 2020 concerning the Implementation of the National Economic Recovery Program in the Context of Supporting State Financial Policies for Handling the Corona Virus Disease 2019 (Covid-19) and / or Facing Threats That Harm National Economy and / or Financial System Stability and Save the National Economy. Keywords: Fiscal Policy, Monetary Policy, Covid -19, Corona Virus